LITERATURE REVIEW OF: THE INFLUENCE OF MANUSIA RESOURCE INFORMATION SYSTEMS, DISCIPLINE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE - Setiyono Setiyono (Dinasti Publisher, 2022)
Previous research or relevant research is very important in a scientific research or article. Previous research or relevant research serves to strengthen the theory and the classification of relationships or influences between variables. This article reviews factors that affect the performance of the community, namely: Human Resource Information Resources, disiplin and kerja motivation, a study of the literature of management of m anusia. The purpose of writing this article is to build a hypothesis of influence between variables to be used in future research. The results of this review literature article are: 1) the provision of information systems sumber daya manusia affects the performance of the pegawai; 2) work disiplin affects employee performance ; and 3) work motivation affects employee performance.